Isolation, Molecular Characterization, Optimization and Purification of Amylase Enzyme from Locally Isolated Bacillus Species in Different Regions of Munshiganj, Bangladesh - Al Kabir, Md Fuadh; Ferdouse , Julia; Kabir, A N M Hamidul (Dhaka University Journal of Pharmaceutical Sciences, 2023)
Amylase is a kind of enzyme that facilitates the breakdown of carbohydrates in the body. This enzyme has many applications in different industries. Generally, in pharmaceutical sector it is used for the treatment of pancreatic disorder, pancreatic enzyme replacement therapy (PERT) and as a digestive aid. In this study, the bacterial strain was isolated from soil samples collected from potato dumpsites in different areas of Munshiganj, Bangladesh. After subculturing on the nutrient agar plate, 31 colonies were obtained, of which 9 isolates were found as amylase producer on starch agar medium. Of these, 2 isolates (MC-04 and MC-15) were selected based on the starch hydrolysis clear zone ratio. The isolate MC-04 showed crude enzyme activity of 2.82 IU/ml and specific enzyme activity of 3.42 IU/mg, and isolate MC-15 showed crude enzyme activity of 3.16 IU/ml and specific enzyme activity of 3.77 IU/mg. The best isolate, MC-15, was then identified by morphology, biochemical and molecular characterization and confirmed by 16S-rRNA gene sequencing. After 16S-rRNA sequencing, the isolate (MC-15) was identified as Bacillus subtilis. This amylase production of this strain had also been optimized under certain conditions such as different incubation periods, pH, temperatures and different carbon sources. We found that the best incubation period was 48 h, the optimum pH-7.0, the optimum temperature at 40°C and 2% starch was considered as the best source of carbon. Finally, the crude amylase enzyme was purified by precipitation with ammonium sulfate, dialysis, and single-step gel filtration chromatography. The enzymatic activity of the purified amylase was found to be 8.91 IU/ml, that was 2.82-fold greater enzymatic activity than the raw enzyme. The experiments confirmed that Bacillus subtilis may be a good source of amylase enzyme for industrial application in Bangladesh. Dhaka Univ. J. Pharm. Sci. 22(2): 147-154, 2023 (December)